A new name and a new combination for Friedmannia nom. illeg. (Hypoxidaceae) - Kocyan, Alexander; Wiland-Szymańska, Justyna (Phytotaxa, 2017)
Recently, Kocyan & Wiland-Szymańska (2016) have published a thorough research article on one of the outstanding members of the family Hypoxidaceae on the Seychelles, which resulted in the raise of a new genus (Friedmannia Kocyan & Wiland-Szymańska 2016: 60) to accommodate the former Curculigo seychellensis Bojer ex Baker (1877: 368). However, it has turned out that the name Friedmannia Chantanachat & Bold (1962: 45) already exists in literature for a green alga, which renders the new hypoxid genus illegitimate (Melbourne Code; McNeill et al. 2012). Therefore, we assign a new generic epithet to Curculigo seychellensis.